Construção do Estado-Providência em Portugal no período do Estado-Novo (1935- 1974): notas sobre a evolução da despesa social - Pereirinha, José A. (2010)
This paper aims at the presentation of some preliminary outcomes from the ongoing research project on the history of the Portuguese welfare state and the process of its construction along the 20th century in the period of Estado-Novo. It is part of the research in its quantitative content, intending the presentation of historical statistical series on social protection in the period 1935-1973. The political decisions on social protection made in this period were significant steps towards the construction of the modern welfare state in Portugal. These time series are then intended to characterize the trend of the institutional organisation of social protection ("previdencia"), of the extent of social risks covered by the social protection system, the amount of the social spending on these social risks and how it was shared by the several institutions as they evolved in this period. This presentation aims at to fill a gap on the knowledge of the trend of social spending in Portugal in this period, intending further research.